Prime Broker-Level Comovement in Hedge Fund Returns: Information or Contagion? - Chung, Ji-Woong; Kang, Byoung Uk (Review of Financial Studies, 2016)
We document strong comovement in the returns of hedge funds sharing the same prime broker. This comovement is driven neither by funds in the same family nor in the same style, and it is distinct from market-wide and local comovement. The common information hypothesis attributes this phenomenon to the prime broker providing valuable information to its hedge fund clients. The prime broker-level contagion hypothesis attributes the comovement to the prime broker spreading funding liquidity shocks across its hedge fund clients. We find strong evidence supporting the common information hypothesis, but limited evidence in favor of the prime broker-level contagion hypothesis.